Qur'anic Contemplation in the Digital Sphere: An Analysis of Qur'an Journaling Practices in Virtual Communities - Abadiah, Sakinatul; Dardum, Abdulloh (QiST: Journal of Quran and Tafseer Studies, 2025)
In this digital era, religious practices are no longer confined to physical spaces but have also been transformed into digital spaces. This phenomenon is represented through the practice of Qur'an journaling which has recently become a trend on several social media platforms as an actualization of the activity of tadabbur al-Qur'an. Therefore, this study aims to determine how tadabbur al-Qur'an is manifested through practice Qur'an journaling that takes place in virtual communities on social media, and to understand the dynamics of meaning and internalization of Qur'anic values in this practice. The theory used in this study is Wolfgang Iser's reception theory to understand the interaction between the text of the Qur'an and readers in practice Qur'an journaling. Using a netnographic approach, data was collected through participant observation, interviews, and documentation of the activities of the Indonesian Al-Qur'an Journal community, which takes place virtually. The research findings show that, the practice Qur'an journaling in this virtual community, it is structured through three stages, namely: Writing verses of the Qur'an along with their translations, understanding verses based on interpretation references and guidance learning menu, and personal reflection that connects the meaning of the verse with the context of everyday life. In this practice, community members take an active role as implied readers who fill in the gaps in the Qur'anic text through their life experiences and personal reflections, thereby forming a process of internalization and actualization of Qur'anic values. These findings indicate that Qur'an journaling is a contemporary form of tadabbur that broadens the understanding and application of the Qur'an in the digital sphere.